PENGEMBANGAN MATERI PEMBELAJARAN BERBASIS TEKNOLOGI UNTUK SISWA TUNANETRA DALAM RANGKA MENINGKATKAN AKSESIBILITAS PENDIDIKAN - Friska Indra Pakelo; Jany Aso; Yustika; Evi Susanti; Janni Toding Bua (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
Education is a fundamental right of every individual, including visually impaired students. However, education accessibility is still a challenge for blind students in acquiring knowledge and information. Therefore, the development of technology-based learning materials becomes an effective solution to improve educational accessibility for blind students. This research aims to develop technology-based learning materials that can be accessed by visually impaired students. The research method used include needs analysis, system design, development of learning materials, as well as testing and evaluation. Learning materials, as well as testing and evaluation. This learning material will be specifically designed to meet the needs of visually impaired students, by using assistive technology devices such as screen readers or braille displays. Development of this technology-based learning material has significant benefits. First, it increases the accessibility of education for blind students, so that they can obtain knowledge and information more easily. They can obtain knowledge and information more easily.  Second, it increases the independence of blind students in learning, because they can access learning materials independently. Third, increasing the motivation of learning through interesting and interactive learning materials. Finally, the development of technology-based learning materials can help reduce the educational gap between blind students and other students. By using technology, students can acquire knowledge and information more effectively. The development of this learning material provides benefits in improving accessibility of education, enhancing independence, increasing motivation to learning, and reducing educational disparities. Therefore further efforts are needed to develop technology-based learning materials that technology-based learning materials that can meet the needs of visually impaired students. In conclusion, the development of technology-based learning material for visually impaired students is an important step in improving accessibility of education for them. By using technology, students can acquire knowledge and information more effectively. The development of this learning material provides benefits in improving accessibility of education, enhancing independence, increasing motivation to learning, and reducing educational disparities. Therefore, further efforts are needed to develop technology-based learning materials that technology-based learning materials that can meet the needs of visually impaired students.